Analysis of the Effectiveness of Labor Supervision in Enforcing the Minimum Wage in Indonesia - Nada Adista Rambe; Aufiya Muhammad Syukri Alghiffary; Darmawan Setia; Ryan Fahri Rangkuti (ISNU Nine-Star Multidisciplinary Journal, 2026)
This study aims to analyze the level of success in the implementation of the labor supervision function in ensuring compliance with the minimum wage provisions in Indonesia. The minimum wage is a basic right of workers that is guaranteed by law, but its implementation in the field still often encounters obstacles. Through a normative juridical research approach, this study examines related laws and regulations, such as Law Number 13 of 2003 concerning Manpower and Government Regulation Number 78 of 2015 concerning Wages, as well as evaluating various previous reports and studies. The results of the analysis show that the effectiveness of labor supervision has not been optimal. The main inhibiting factors include the limited number of supervisory personnel, inadequate budget and infrastructure, and the lack of strict sanctions against violators. Comprehensive efforts are needed, both in terms of strengthening regulations, building institutional capacity, and consistent law enforcement, to increase the effectiveness of supervision in order to guarantee workers' rights to a real minimum wage.